Nutritional and Pharmacological Effects on Oxidative Stress in Soft Tissue and Bone Remodeling - Benjamin M. Savasky; David P. Mascotti; Naren Patel; Edgardo Rodriguez-Collazo (Journal of Nutrition and Metabolism)
Oxidative damage is the causal link to a multitude of pathologies, such as diabetes, arthritis, neuropathy, heart disease, and asthma. These conditions affect hundreds of millions of people nationwide, and billions worldwide. Even in otherwise healthy individuals, oxidative stress is a natural byproduct of metabolism that is augmented in “healthy” activities such as athletics. In many disease states, the pharmacological agents used to treat these conditions can induce oxidative damage and vitamin depletion. It is underappreciated by many that many of the most common medications prescribed result in oxidative stress. Therefore, physicians need to carefully scrutinize which medications their patients are on before surgery and treatment and during the recovery stage to obtain optimal healing results. We provide a review of the current literature of how oxidative damage and inflammation are linked to bone damage, Charcot neuroarthropathy, delayed wound healing, diabetic complications, and delayed flap consolidation. Where available, antioxidant intervention literature is offered to offset these conditions.